Development of Learning Media Using the Smart Apps Creator Application on Human Respiratory System Material of Science for Class V Elementary School - Wahyuni, Ayu; Hendri, Nofri; Eldarni, Eldarni; Supendra, Dedi (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to produce learning media in accordance with development procedures using standard criteria of validity and practicality so that it becomes a learning media that is suitable for use in the learning process. The type and method of this research is development research or better known as Research and Development (R&D) , using a 4-D development model. The development procedure in this research consists of 4 stages, namely; (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validation test was carried out by 3 validators, namely 2 media validators and 1 material validator. Product trials were carried out on 20 class V students of SD Negeri 08 Talao with the aim of finding out the practicality of the product being developed. The results of this research explain that the assessment from media validators was declared "Very Valid" with an average of validator I of 4.93 with a percentage level of 98.6% and media validators with an average of 4.87 with a percentage level of 97.4%. The material validator results were declared "Very Valid" with an average of 4.86 with a percentage of 97.2%. The results of the practicality trial analysis were declared "Very Practical" with an overall average of 4.78 or a percentage of 95.6%. So it can be concluded that the learning media in the Human Respiratory System material for class V Elementary School Science that was developed is very valid and very practical. So learning media is suitable for use in the learning process.